Dominant immunosuppression of dendritic cell function by prostate-cancer-derived exosomes. Issue 1 (1st December 2017) - Salimu, Josephine; Webber, Jason; Gurney, Mark; Al-Taei, Saly; Clayton, Aled; Tabi, Zsuzsanna
ABSTRACT: Exosomes are a distinct population of extracellular vesicles of endocytic origin with a protein repertoire similar to the parent cell. Although tumour-derived exosomes harbour immunosuppressive characteristics, they also carry tumour antigens and thus potentially contribute to immune activation. The aim of this study was to examine the impact of prostate cancer exosomes on tumour antigen cross-presentation. DU145 cells, transduced with shRNA to knockdown Rab27a (DU145 KD ) that inhibits exosome secretion, triggered significantly stronger tumour-antigen-specific T cell responses when loaded onto dendritic cells (DC) than control DU145 cells. Enhanced T cell response was prevented by adding purified exogenous DU145 exosomes to DU145 KD cells, demonstrating that the dominant effect of tumour exosomes is immunosuppression and not antigen delivery. CD8 + T cell responses were impaired via exosomal regulation of DC function; exosomes triggered the expression of CD73, an ecto-5-nucleotidase responsible for AMP to adenosine hydrolysis, on DC. CD73 induction on DC that constitutively express CD39 resulted in an ATP-dependent inhibition of TNFα- and IL-12-production. We identified exosomal prostaglandin E2 (PGE2 ) as a potential driver of CD73 induction, as inhibition of PGE2 receptors significantly reduced exosome-dependent CD73 induction. The results reveal a hitherto unknown suppression of DC function via exosomal PGE2, adding a new element to tumour exosome–immune cell cross-talk. Abbreviations : AMP: adenosine monophosphate; ATP: adenosine triphosphate; BLCL: B lymphoblastoid cell line; CME: exosomes enriched from cell line conditioned media; DC: dendritic cell; DMSO: dimethyl-sulfoxide; DU145 C : DU145 cells with irrelevant knockdown control; DU145 KD : DU145 cells with Rab27a knockdown; ELISA: enzyme-linked immunosorbent assay; FBS: fetal bovine serum; GM-CSF: granulocyte-monocyte colony stimulating factor; HLA: human lymphocyte antigen; IL: interleukin; LPS: lipopolysaccharide; mfi: mean fluorescence intensity; PBMC: peripheral blood mononuclear cells; PBS: phosphate buffer solution; PGE2 : prostaglandin E2 ; TRF: time-resolved fluorescence.